2018
DOI: 10.1016/j.exppara.2018.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Anti-infective activities of 11 plants species used in traditional medicine in Malaysia

Abstract: Treatment of drug resistant protozoa, bacteria, and viruses requires new drugs with alternative chemotypes. Such compounds could be found from Southeast Asian medicinal plants. The present study examines the cytotoxic, antileishmanial, and antiplasmodial effects of 11 ethnopharmacologically important plant species in Malaysia. Chloroform extracts were tested for their toxicity against MRC-5 cells and Leishmania donovani by MTT, and chloroquine-resistant Plasmodium falciparum K1 strain by Histidine-Rich Protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…About antimicrobial activity, various lignans have exhibited antiviral and antibacterial activity, e.g., against Gram-positive bacteria through alteration of biofilm formation, bacteria metabolites, membrane receptors and ion channels [98]. For instance, pinoresinol has demonstrated activity against some virus [99].…”
Section: Human Studies Concerning Lignan Bioactivitymentioning
confidence: 99%
“…About antimicrobial activity, various lignans have exhibited antiviral and antibacterial activity, e.g., against Gram-positive bacteria through alteration of biofilm formation, bacteria metabolites, membrane receptors and ion channels [98]. For instance, pinoresinol has demonstrated activity against some virus [99].…”
Section: Human Studies Concerning Lignan Bioactivitymentioning
confidence: 99%
“…The antimicrobial activity against tested microbes including Staphylococcus aureus (ATCC29213), Escherichia coli (ATCC25922), and Candida albicans (ATCC 10231) at 10 µg/ml concentration revealed that all the compounds screened did not show inhibitory activity (for information detail; see Table S4). According to literature reports, the crude extracts and pure compounds isolated from various parts of U. grandiflora were examined for several biological activities such as cytotoxic, anti-inflammatory, antioxidant, and antimicrobial activities [6][7][8][9][20][21][22]. To the best our search from SciFinder database, compounds 1-6 have never been investigated for their antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…have also been reported, including extracts and alkaloids from T. citrifolia on the gastrointestinal nematode Haemonchus contortus [22], T. elegans, T. pachysiphon, T. peduncularis and T. macrocarpa on the malarial protozoan Plasmodium falciparum [23][24][25][26], T. pandacaqui on the protozoan Trypanosoma cruzi, causal agent of Chagas disease [27] and T. longipes on Trypanosoma brucei, causal agent of African sleeping sickness [28]. Previous phytochemical research has shown T. arborea root bark to be particularly rich in monoterpenoid indole alkaloids (MIAs), including ibogaine, voacangine, and vobasine, as well as the bis-indole type alkaloid voacamine [21,29].…”
Section: Accepted Manuscriptmentioning
confidence: 99%